Dinamika Pendidikan Multikultural: Sintesis Perspektif Teoritis - Arga Dwi Praditya; Moch. Iqbal (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The purpose of this discussion is to see how the dynamics of multicultural education in the surrounding environment, based on the definition, purpose, basis, how multicultural and cultural education diffusion, as well as the conceptual framework. Where the methodology used in this research is in the form of Library Research, namely researchers utilize research methods by collecting, studying, and understanding sources regarding multicultural education, Data collection in this method is using how to analyze and reconstruct existing references, such as books, journal articles, and studies that have been carried out by previous research. Study materials obtained from sources in the form of scientific articles both national and international, books, magazines, online news. multicultural education is needed as an effort to transform awareness so that differences in culture, customs, religion, and ethnicity can be embraced. Multicultural education also teaches a culture that has always existed until now.